Traditional usage of wild edible plants reflecting the dietary habits and the awareness of health care of LI minority in Baoting and Lingshui, Hainan Island, China: An ethnobotanical approach - Yang, Dongmei; Liu, Xiying; Fan, Pingling; Wu, Yougen (Bangladesh Journal of Botany, 2019)
Traditional usage of wild edible plants reflect the dietary habits as they have potential medicinal functions and the awareness of health care of Li Minority in Hainan Island. To facilitate the use and development of wild edible plants in Hainan Island, information was collected four times by semi-structured interviews in 17 traditional markets of Baoting and Lingshui. Twenty six species belonging to 24 genera under 16 families of vascular plants were recognized as wild edible plants. 84.62% of the total species were annual and perennial herbs. Above ground parts were the most frequently used parts. The most common preparation mode was plain-frying. Heat-clearing was the most common medicinal function. Weather, the size of population and plant diversity in local areas have close relationship with the species richness of wild edible plants traded in traditional markets. Geographical difference and time are not critical for the fluctuation of price.